Volatile Metabolomic Composition of Vitex Species: Chemodiversity Insights and Acaricidal Activity - de Sena Filho, José G.; Barreto, Ighor C.; Soares Filho, Avaldo O.; Nogueira, Paulo C. L.; Teodoro, Adenir V.; Cruz da Silva, Ana V.; Xavier, Haroudo S.; Rabbani, Allívia R. C.; Spakowicz, Daniel J.; Duringer, Jennifer M. (Frontiers in Plant Science, 2017)
The Vitex genus (Lamiaceae) produces a plethora of metabolites that include ecdysteroids and terpenoids, some of which have demonstrated insect repellent properties. The volatile composition of several members of this genus has not been chemically defined, as many taxa are endemic to remote ecosystems. In this study, leaves were collected from the northeast of Brazil from Vitex capitata, V. megapotamica, V. gardneriana and V. rufescens plants and examined for their chemical profile via GC-MS/FID of essential oil extracts. The analyses showed a diversity of terpenoids. Of particular note were seven-member ring sesquiterpenes which were present in great abundance; a dendrogram showed clades separating by the production of (+)-bicyclogermacrene, aromadendrane and 5,10-cycloaromadendrane sesquiterpenoids for the four species. Comparison of volatile metabolite profiles to 13 other Vitex species showed strong similarities in the production of some monoterpenes, but varied by their production of larger terpenes, especially those with gem-dimethylcyclopropyl subunits on seven-member ring compounds. From this work, we suggest that the sesquiterpene skeleton with seven member rings is a good chemosystematic biomarker candidate for the Vitex genus. Separation using this biomarker was then validated using Inter-Simple Sequence Repeat (ISSR) profiling. Lastly, experiments examining the toxicity of these four oils against the coconut mite A. guerreronis showed that only the oil of V. gardneriana had strong acaricidal activity, with an LC50 of 0.85 mg/mL, thus demonstrating its potential for use as a natural pesticide.